Chronic Subdural Hematoma (CSDH) score for predicting outcome in CSDH in a tertiary care center in Nepal - Karki, Anjan; Gurung, Ashim; Thapa, Bikash; Phuyal, Suman; Pradhanang, Amit B; Bhandari, Binod Raj; Sedain, Gopal; Shilpakar, Sushil Krishna; Sharma, Mohan Raj (Nepal Journal of Neuroscience, 2025)
Introduction: Chronic subdural hematoma (cSDH) presents a significant neurosurgical challenge, particularly in elderly patients and those with predisposing factors such as chronic alcohol consumption or coagulopathies. While burr-hole evacuation is the standard surgical technique, alternative approaches exist. The cSDH score, incorporating variables such as age, Glasgow Coma Scale (GCS), hematoma thickness, midline shift, motor function, and orientation, offers a comprehensive assessment tool. This study aims to evaluate the cSDH score's predictive ability for outcomes in chronic SDH patients using the Modified Rankin Scale (mRS) at discharge and after six months.Methods: Patients diagnosed with unilateral chronic subdural hematoma at Tribhuvan University Teaching Hospital between December 2019 and April 2021 were included. Data on cSDH score variables were collected at admission, and outcomes were assessed using mRS at discharge and after six months. Analysis included receiver-operating characteristic (ROC) curve to evaluate discrimination ability and analysis of variance to assess predictive variables.Results: The study comprised 74 patients, with headache being the most common presentation. At discharge, fifty-five patients (74.3%) of patients had favorable outcomes, increasing to fifty-six patients (75.7%) after six months. Analysis indicated associations between preoperative GCS, age, hematoma thickness, midline shift, motor function, orientation, and unfavorable mRS outcomes. ROC analysis demonstrated excellent discrimination ability of the cSDH score, with AUCs of 0.936 at discharge and 0.948 after six months.Conclusion: The cSDH score proves valuable in predicting outcomes for chronic subdural hematoma patients. However, largermulticenter studies are needed to validate the predictive ability of the score in patients with chronic subdural hematoma.